Pharmacokinetic characterization of BMS‐936561, an anti‐CD70 antibody‐drug conjugate, in preclinical animal species and prediction of its pharmacokinetics in humans. (15th May 2015) - Wang, Haiqing; Rangan, Vangipuram S.; Sung, Mei‐Chen; Passmore, David; Kempe, Thomas; Wang, Xiaoli; Thevanayagam, Lourdes; Pan, Chin; Rao, Chetana; Srinivasan, Mohan; Zhang, Qian; Gangwar, Sanjeev; et al.
Abstract: CD70 is a tumor necrosis factor (TNF)‐like type II integral membrane protein that is transiently expressed on activated T‐ and B‐lymphocytes. Aberrant expression of CD70 was identified in both solid tumors and haematologic malignancies. BMS‐936561 ( α CD70_MED‐A) is an antibody‐drug conjugate composed of a fully human anti‐CD70 monoclonal antibody ( α CD70) conjugated with a duocarmycin derivative, MED‐A, through a maleimide‐containing citrulline‐valine dipeptide linker. MED‐A is a carbamate prodrug that is activated by carboxylesterase to its active form, MED‐B, to exert its DNA alkylation activity. In vitro serum stability studies suggested the efficiencies of hydrolyzing the carbamate‐protecting group in α CD70_MED‐A followed a rank order of mouse > rat > > monkey > dog ~ human. Pharmacokinetics of α CD70_MED‐A was evaluated in mice, monkeys, and dogs after single intravenous doses. In mice, α CD70_MED‐A was cleared rapidly, with no detectable exposures after 15 min following dosing. In contrast, α CD70_MED‐A was much more stable in monkeys and dogs. The clearance of α CD70_MED‐A in monkeys was 58 mL/d/kg, ~2‐fold faster than that in dogs (31 mL/d/kg). The human PK profiles of the total α CD70 and α CD70_MED‐A were predicted using allometrically scaled monkeys PK parameters of α CD70 and the carbamate hydrolysis rate constant estimated in dogs. Comparing the predicted and observed human PK from the phase I study, the dose‐normalized concentration‐time profiles of α CD70_MED‐A and the total α CD70 were largely within the 5 th ‐95 th percentile of the predicted profiles. Copyright © 2015 John Wiley & Sons, Ltd.